2016
DOI: 10.1007/s10653-016-9842-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of woody biomass and biochar for alleviating heavy metal bioavailability in serpentine soil

Abstract: Crops grown in metal-rich serpentine soils are vulnerable to phytotoxicity. In this study, Gliricidia sepium (Jacq.) biomass and woody biochar were examined as amendments on heavy metal immobilization in a serpentine soil. Woody biochar was produced by slow pyrolysis of Gliricidia sepium (Jacq.) biomass at 300 and 500 °C. A pot experiment was conducted for 6 weeks with tomato (Lycopersicon esculentum L.) at biochar application rates of 0, 22, 55 and 110 t ha. The CaCl and sequential extractions were adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…The decrease in the yield at high pyrolysis temperatures could be ascribed to the loss of volatile components, and the high ash content of the biochar indicates the accumulation of inorganic minerals, which could raise the pH and CEC 20,21 . Previous studies have shown that a high pH value for biochar may result from the release of alkali salts and the loss of acidic functional groups 22 . The elemental composition of PC and SC is shown in Table 1; very small amounts (≤0.20%) of other elements (e.g., S, Ca, Mn, Ag, Cr, and Cd) were detected, and the contents of these elements are not given in the table.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the yield at high pyrolysis temperatures could be ascribed to the loss of volatile components, and the high ash content of the biochar indicates the accumulation of inorganic minerals, which could raise the pH and CEC 20,21 . Previous studies have shown that a high pH value for biochar may result from the release of alkali salts and the loss of acidic functional groups 22 . The elemental composition of PC and SC is shown in Table 1; very small amounts (≤0.20%) of other elements (e.g., S, Ca, Mn, Ag, Cr, and Cd) were detected, and the contents of these elements are not given in the table.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar amendments onto contaminated soils would greatly reduce the total metal concentration and bioavailability fraction [23][24][25][26]. For instance, Ahmad et al [27] found that soybean stover-derived BC more efficiently immobilized Pb (88%) and Cu (87%) in shooting range soil in Cheorwon-gun in Gangwon-do, Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, biochars are recalcitrant from degradation (Cernansky, 2015 ) and characterized with lower labile C fractions (Zimmerman et al, 2011) and rich functional groups for metal retention (Dong et al, 2014). For example, biochars are able to immobilize nickel, chromium, and Mn in heavy metal contaminated serpentine soil (Bandara et al, 2016). On other hand, the metal compounds in the biomass can be converted to their more stable forms.…”
Section: A Practical Solution To Disposal Of Heavy Metal Hyper-accumumentioning
confidence: 99%